DEVELOPMENT OF PERSPECTIVE CRIMINAL LAW INDONESIAN NOBLE VALUES - Muchamad Iksan; Sri Endah Wahyuningsih (Universitas Muhammadiyah Ponorogo, 2020)
The existence of criminal law is to protect and maintain central values insociety. As an independent nation, the applicable criminal law should be in accordancewith the noble values that live and develop in Indonesian society. KUHP (WvS) is aproduct of western colonial law, of course it carries the spirit of colonialism,individalism, and liberalism that is not in accordance with the noble values of anindependent Indonesian nation. The development of Indonesian criminal law must bebased on Indonesian philosophy, spirit, and values, in terms of ideology (Pancasila),religious/religious, social, political, economic, and cultural aspects that live anddevelop in society (customary law). Nor should it ignore international developments,because the Indonesian state is part of a civilized international community. Colonialinheritance criminal law that adheres to the teachings of positivist legal law, must beintegrated with the teaching of legal historism which is a legal understanding that isconsidered appropriate and adhered to by the people of Indonesia, so that in Indonesiathere is an unwritten criminal law (customary criminal law).